The innocent murmurs - Ahmad H. Asdie, Ahmad H. Asdie (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1981)
In this article the innocent murmur includes only those murmurs that are associated with no known abnormality, either structural or physiologic. The term "functional murmur" and "physiologic murmur" are avoided, because they may include even murmurs resulting from dilatadon of valves, heart chamber, and vessels or are associated with acceleration of the circulation.The innocent murmurs are common and are often misinterpreted. Misinterpretation of innocent murmurs may lead to anxiety on the part of both physician and patient, to a prolonged period of unnecessary restriction of physical activity, and perhaps to permanent cardiac neurosis. They may also lead to exclusion of healthy young people from athletic activities, flying, and military service, or to the use of unnecessary prophylactic penicillin. The distinction between an organic murmur and an innocent murmur is enlargement, no history of rheumatic fever; absence of cyanosis, clubbing, and congestive heart failure.KeyWords: innocent murmur - functional murmur- physiologic murmur - venous hum